Silage mycotoxins - Oliveira, Eduarda; Grossi de Sousa, Pamella; Lobato Menezes, Guilherme; Figueiredo de Oliveira, Alan; Patrus Ananias de Assis Pires, Frederico; Araújo de Menezes, Rafael; Da Silva, Ana Eliza; Gonçalves, Lúcio Carlos; Gonzaga Jayme, Diogo (Pubvet, 2022)
The silage process consists of preserving green forage. However, errors in operations during harvesting, or even at the opening of the silo, can result in colonization of fungi and production of mycotoxins. Therefore, it is important to develop strategies to mitigate the negative effects of mycotoxins in the feeding of dairy cows. The objective was to review the literature on the contamination of silage by mycotoxins, including predisposing factors for contamination and ways of prevention and mitigation. The main environmental conditions that favor mycotoxin synthesis are temperature, pH and water activity. In addition, factors linked to the operation, such as delayed harvesting, delays in sealing the silo, the density of compaction or the use of damaged seals also favor fungal growth. The control of these processes in silage aims to avoid contamination by toxinogenic fungi. However, current control strategies are not entirely effective. Some safe and relatively economical measures are the use of mycotoxin adsorbents or bacterial inoculants, which can be used to reduce the absorption of mycotoxins in the gastrointestinal tract.